EXTRACTIVE SPECTROPHOTOMETRIC DETERMINATION OF IRON (III) WITH 5-(P-HYDROXYBENZYLIDENE)-THIAZOLIDINEDIONE-2,4 - N. A, Verdizade; K. A, Kuliev; K. R., Alieva (IJRDO-Journal of Applied Science, 2016)
5-(p-hydroxybenzylidene)-Thiazolidinedione-2,4 (L) as a photometric reagent for the extractive spectrophotometric determination of iron(III) is presented in this paper. The reagent L gave instantaneous and stable red colour with iron (III) in the pH range 3.8 to 5.2. The Beer’s law was applicable in the range of 0.05 - 3.2μg/ml at 535 nm. The Limit of Detection (LOD) is found to be 12 ng/mL. The stoichiometry of the complex is established as 1:2 (Fe: L) by equilibrium shift method. The standard deviation and the coefficient of variance are presented. The results of the prescribed procedure applied for the determination of the micro amounts of Fe (III) in pharmaceutical, food and in plant samples are presented.